A new species and new combination in Salpichroa, Solanaceae / S. H. Kuo Keel - Kuo Keel, Shirley H. (2007)
A monographic study of the genus Salpichroa revealed a new species, S. microloba, and one taxon with a new status, S. glandulosa subsp. weddellii. These taxa are discussed and information on their probable relatinships is given
il. byn
Keywords: Solanaceae; Salpichroa